Overexpression of Isoforms of Nitric Oxide Synthase 1 Adaptor Protein, Encoded by a Risk Gene for Schizophrenia, Alters Actin Dynamics and Synaptic Function - Hernandez, Kristina; Swiatkowski, Przemyslaw; Patel, Mihir V.; Liang, Chen; Dudzinski, Natasha R.; Brzustowicz, Linda M.; Firestein, Bonnie L. (Frontiers in Cellular Neuroscience, 2016)
Proper communication between neurons depends upon appropriate patterning of dendrites and correct distribution and structure of spines. Schizophrenia is a neuropsychiatric disorder characterized by alterations in dendrite branching and spine density. Nitric oxide synthase 1 adaptor protein (NOS1AP), a risk gene for schizophrenia, encodes proteins that are upregulated in the dorsolateral prefrontal cortex of individuals with schizophrenia. To elucidate the effects of NOS1AP overexpression observed in individuals with schizophrenia, we investigated changes in actin dynamics and spine development when a long (NOS1AP-L) or short (NOS1AP-S) isoform of NOS1AP is overexpressed. Increased NOS1AP-L protein promotes the formation of immature spines when overexpressed in rat cortical neurons from day in vitro (DIV) 14 to DIV 17 and reduces the amplitude of miniature excitatory postsynaptic currents (mEPSCs). In contrast, increased NOS1AP-S protein increases the rate of actin polymerization and the number of immature and mature spines, which may be attributed to a decrease in total Rac1 expression and a reduction in the levels of active cofilin. The increase in the number of mature spines by overexpression of NOS1AP-S is accompanied by an increase in the frequency of mEPSCs. Our findings show that overexpression of NOS1AP-L or NOS1AP-S alters the actin cytoskeleton and synaptic function. However, the mechanisms by which these isoforms induce these changes are distinct. These results are important for understanding how increased expression of NOS1AP isoforms can influence spine development and synaptic function.